2017
DOI: 10.23861/ejbm201631752
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Schizophrenia: A Closer Look at How Dysregulation of Neuronal Cell Homeostasis Influences the Pathogenesis of Schizophrenia

Abstract: Autophagy, the process of degrading intracellular components in lysosomes, plays an important role in the central nervous system by contributing to neuronal homeostasis. Autophagic failure has been linked to neurologic dysfunction and a variety of neurodegenerative diseases. Recent investigation has revealed a novel role for autophagy in the context of mental illness, namely in schizophrenia. This article summarizes the phenomenology, genetics, and structural/histopathological brain abnormalities associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…This is supported by evidence showing that, mutations or dysfunctions of Rabs, SNAREs and Endophilin-A, which directly affect ATG, associate with several DA-synaptic disorders ranging from PD to drug addiction and schizophrenia (Drouet and Lesage, 2014 ; Katrancha and Koleske, 2015 ; Vanderwerf et al, 2015 ; Shi et al, 2017 ). On the other hand, ATG induction via mTOR or GSK3β ameliorates early psychomotor and cognitive behavioral alterations by rescuing neurotransmission defects in these same disorders (Schneider et al, 2016 ; Huang et al, 2018 ; Kara et al, 2018 ; Masini et al, 2018 ). In such a tightly interconnected mechanism, it is mandatory to further investigate the UP, which is also modulated by mTOR and co-localizes with ATG (Lenzi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by evidence showing that, mutations or dysfunctions of Rabs, SNAREs and Endophilin-A, which directly affect ATG, associate with several DA-synaptic disorders ranging from PD to drug addiction and schizophrenia (Drouet and Lesage, 2014 ; Katrancha and Koleske, 2015 ; Vanderwerf et al, 2015 ; Shi et al, 2017 ). On the other hand, ATG induction via mTOR or GSK3β ameliorates early psychomotor and cognitive behavioral alterations by rescuing neurotransmission defects in these same disorders (Schneider et al, 2016 ; Huang et al, 2018 ; Kara et al, 2018 ; Masini et al, 2018 ). In such a tightly interconnected mechanism, it is mandatory to further investigate the UP, which is also modulated by mTOR and co-localizes with ATG (Lenzi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, as Shank3 interacts with the autophagy‐regulator mTOR, and with Shank proteins being implicated in both schizophrenia and ASD, future investigation should be aimed at testing possible interplay of SHANK with ADNP. Furthermore, autophagy may be pharmacologically targeted in neuropsychiatric disorders, and in this regard, normalization of BECN1 expression levels, as well as those of ADNP and ADNP2 introduces a new strategy for treating schizophrenia. Thus, NAP presents a different approach on top of traditional schizophrenia treatments (antipsychotics), which act through D2 receptors blockade, and produce a high rate of extrapyramidal symptoms as side effects.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, autophagy may serve as a potential target for pharmacological intervention, generally in human diseases, and specifically in neuropsychiatric disorders . One of the action mechanisms of several antipsychotic medications, including lithium, fluspirilene, trifluoperazine and pimozide, is through autophagy induction . Nevertheless, this is not always the case.…”
Section: Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…It constitutes a major protective mechanism that allows cells to survive in response to multiple stressors and helps to defend organisms against degenerative, inflammatory, infectious and neoplastic diseases [55][56][57]. Importantly, several studies have shown its crucial role in the development and pathology of schizophrenia [58,59]. To study whether ketamine induces autophagy, NSCs were incubated with 400 μM ketamine for 24 h and/or co-treated with 10 nM clozapine whereupon the level of the autophagosome marker LC3-II was assessed.…”
Section: Clozapine Counteracts Ketamine-induced Decrease In Nsc Viabimentioning
confidence: 99%